2017
DOI: 10.1111/acel.12703
|View full text |Cite
|
Sign up to set email alerts
|

17α‐estradiol acts through hypothalamic pro‐opiomelanocortin expressing neurons to reduce feeding behavior

Abstract: SummaryWeight loss is an effective intervention for diminishing disease burden in obese older adults. Pharmacological interventions that reduce food intake and thereby promote weight loss may offer effective strategies to reduce age‐related disease. We previously reported that 17α‐estradiol (17α‐E2) administration elicits beneficial effects on metabolism and inflammation in old male mice. These observations were associated with reduced calorie intake. Here, we demonstrate that 17α‐E2 acts through pro‐opiomelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 14 publications
11
31
0
Order By: Relevance
“…Almost immediately after 17α-E2 treatment began, WT mice displayed significant reductions in mass (Figure 2A-B) and adiposity ( Figure 2C-D). This is aligned with our previous reports demonstrating that 17α-E2 administration quickly reduced body mass and adiposity [22][23][24], which we have linked to hypothalamic regulation of anorexigenic signaling pathways [23]. Indeed, WT mice in the current study also displayed robust declines in calorie consumption during the first four weeks of treatment ( Figure 2E).…”
Section: Erα Ablation Attenuates 17α-e2-mediated Benefits On Metabolisupporting
confidence: 93%
See 2 more Smart Citations
“…Almost immediately after 17α-E2 treatment began, WT mice displayed significant reductions in mass (Figure 2A-B) and adiposity ( Figure 2C-D). This is aligned with our previous reports demonstrating that 17α-E2 administration quickly reduced body mass and adiposity [22][23][24], which we have linked to hypothalamic regulation of anorexigenic signaling pathways [23]. Indeed, WT mice in the current study also displayed robust declines in calorie consumption during the first four weeks of treatment ( Figure 2E).…”
Section: Erα Ablation Attenuates 17α-e2-mediated Benefits On Metabolisupporting
confidence: 93%
“…Given the close association between adiposity and metabolic homeostasis, coupled with our previous work demonstrating the ability of 17α-E2 to improve metabolic parameters [22,23], we also assessed several metabolic variables in these studies. Similar to the mass and adiposity data described above, WT mice receiving 17α-E2 displayed significant improvements in fasting insulin ( Figure 3B Supplementary Figure 1); whereas ERα KO mice receiving 17α-E2 failed to recapitulate these findings.…”
Section: Erα Ablation Attenuates 17α-e2-mediated Benefits On Metabolimentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that some responses to 17aE2, particularly changes in feeding behavior, are dependent on the presence of functional POMC neurons (Steyn et al 2018), although other metabolic responses to 17aE2 remain intact. The ARC of the hypothalamus, where we observe changes in the expression of ERα and reduced inflammation with 17aE2, contains POMC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a subsequent study, it was shown that some of the short-term metabolic responses to 17aE2, particularly feeding behavior on a high-fat diet, are dependent on the functional presence of pro-opiomelanocortin (POMC) neurons (Steyn et al 2018), a subset of neurons found in the arcuate nucleus of the hypothalamus (ARC). This indicates that hypothalamic actions of 17aE2 are involved in some of the metabolic responses to this drug, at least in the context of obesity.…”
Section: Introductionmentioning
confidence: 99%